SEX DIFFERENCES IN ANTERIOR CRUCIATE LIGAMENT INJURIES AMONG US HIGH SCHOOL SOCCER PLAYERS: AN EPIDEMIOLOGIC STUDY. Issue 3 (31st March 2019) - Gupta, Andrew; Pierpoint, Lauren; Comstock, Dawn; Saper, Michael
BACKGROUND: Anterior cruciate ligament (ACL) injuries are common among adolescent athletes, with soccer being the sport most frequently implicated in girls' ACL injuries. The current literature on ACL injuries, while extensive, lacks a comprehensive study of ACL injuries in United States (US) high school soccer players. The objective of this study was to describe the epidemiology of ACL injuries among US high school soccer players. METHODS: ACL injury and athlete exposure (AE) data for US high school soccer players were obtained from the internet-based National High School Sports-Related Injury Surveillance System, High School RIO (Reporting Information Online) dataset collected from school years 2007-2008 through 2016-2017. Injury rates were calculated as the number of ACL injuries per 100, 000 AEs. Subgroup differences were evaluated with rate ratios (RRs) or injury proportion ratios (IPRs) and 95% Confidence Intervals (CIs). Subgroup differences were examined with independent t-tests. Comparisons of categorical data (i.e., mechanism of injury) were performed using Pearson's?2 tests. RESULTS: The number of ACL injuries reported to High School RIO corresponded to weighted national estimates of 41, 205 (95% CI = 33, 321 – 48, 730) ACL injuries in boys' soccer and 110, 029 (95% CI = 95, 349 – 124, 709) in girls' soccer during the study period. ACL injury rates were significantly higher in girls' soccer (13.23 per 100, 000 AEs) than boys' soccer (4.35 per 100, 000 AEs) (RR = 3.04, 95% CI = 2.35 – 3.98) and were significantly higher in competition compared to practice for both girls (RR = 14.77, 95% CI = 9.85 – 22.15) and boys (RR = 8.69, 95% CI = 5.01 – 15.08). A greater proportion of ACL injuries were due to player-player contact in boys (48.6%) compared to girls (30.1%) (IPR = 1.62, 95% CI = 1.08 – 2.42). There was no statistical difference in the proportion of ACL injuries managed surgically in boys and girls (84% vs. 78%, respectively). CONCLUSIONS: There are sex-based differences in mechanism of injury and ACL injury rate in high school soccer players. In addition, boys and girls showed higher rates of injury during competition. This study suggests several areas for targeted evidence-based ACL injury prevention strategies in US high school soccer players.